Pest Complex of Mung Bean in India - Verma, S K; Saxena, R C (Annals of Arid Zone, 2016)
Pests recorded on mung bean in India have been reviewed and a check list of the pests has been given. The pests listed include 14 genera and 22 species of Coleoptera, 3 genera and species of Diptera, 16 genera and 23 species of Hemiptera, a single species of Hymenoptera, 28 genera and 34 species of Lepidoplera. 4 genera and species of Orthoptera. and 2 genera and species of Thysanoptera among the insects, 12 species of nemalodes representing 8 genera, 2 genera and species of mites and a millipede species. Weevils Ataclogaster oriellfa/is (Chevrolat) and Myllocerus /aetivirens Marshall (Curculionidae:Coleoptera) and the spiltle bug Poophilus costalis Walker (Aphrophoridae: Hemiptera) are new records on mung bean in Rajasthan.